Optimal Allocation of Water Resources in Tarim River Basin Based on Engineering Pattern Optimization - HONG Liangpeng; BAI Tao; LI Jiang; LIU Dong (Renmin Zhujiang)
In order to optimize engineering layout, alleviate the contradiction between water supply and demand, and improve the comprehensive utilization efficiency of water resources in the basin, this study took the sources of the Tarim River including the Aksu River, Hotan River, and Yeerqiang River and its main streams as the research objects. In response to problems such as the large evaporation and seepage losses of plain reservoirs within the river basin and the prominent contradiction between supply and demand of water resources, a joint allocation model of reservoir groups was established and solved. The research results show that a scheme for replacing plain reservoirs in the main streams with mountainous reservoirs has been developed and optimized. By replacing the plain reservoir groups in the main streams, the total water shortage and water loss in the basin can be significantly reduced, and the contradiction between water supply and demand in the basin can be eased. On the basis of meeting the demand for industrial and domestic water, properly reducing the water discharge in the source area can greatly alleviate the water contradiction between the source area and the main stream area and improve the irrigation water supply in the basin. Under the objective of optimized planning, a water resources allocation scheme is made. To be specific, under the condition of average water supply for many years, the water supply for agricultural irrigation and ecological water supply outside the river are 13.502 billion m3 and 1.404 billion m3, respectively. The research results provide technical support for guiding the abandonment of plain reservoirs and have scientific guiding significance and demonstration value for ecological protection and sustainable utilization of water resources in similar basins in arid areas.